Self-adhesive material as well as preparation method and application thereof
By developing a self-adhesive material, the cross-linking reaction of citrate-based prepolymer and isocyanate is solved, and the existing anti-adhesive biofilm materials need to be sewn and fixed and biocompatibility are achieved, achieving the effects of self-adhesive, degradable and good biocompatibility.
Patent Information
- Application Number
- CN202510194327.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-21
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2045-02-21
AI Technical Summary
Existing anti-adhesion biofilm materials need to be sewn and fixed, which increases the difficulty of surgical operation and infection risk, and the degradation rate, mechanical strength and tissue biocompatibility are difficult to satisfy.
A self-adhesive material is developed to form a citrate-based prepolymer by reacting component A and component B and cross-linking with isocyanate urethane bonds or amide bonds to form a material with self-adhesive, degradable and good biocompatibility.
Due to its self-adhesion, this material can be fixed without suture, reduces the difficulty of surgical operation and infection risk, and is completely degradable in the body, with satisfactory degradation rate, mechanical strength and histocompatibility.
Smart Images

Figure CN119680022A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of biomedical materials, and in particular to a self-adhesive material, a preparation method and use thereof. Background Art
[0002] Biofilms in the field of biomedical materials are generally used as materials to replace and repair human tissues. According to different application scenarios, such as wound dressings, medical adhesives, anti-adhesion membranes, etc. Among them, the role of anti-adhesion membranes is to prevent tissue adhesion. Tissue adhesion refers to a pathological state in which the contact surfaces of adjacent tissues or organs are connected by cellulose in scar tissue or new fibrous tissue. It is a common clinical phenomenon after surgery and a necessary process for patients to heal. The formation of adhesions is usually related to surgery, trauma, inflammation, infection, or foreign bodies in the abdominal cavity. For example, tendon adhesions are closely related to the tendon healing process and can be divided into two mechanisms: endogenous and exogenous healing. Endogenous healing achieves tendon healing through the proliferation of fibroblasts on the surface of the tendon, which can prevent tendon adhesion. Exogenous healing involves the formation of new granulation tissue on the tendon fracture surface by the subcutaneous tissue and synovium of the tendon, forming scar tissue, leading to adhesion. In addition, destruction of tendon blood supply and integrity and inflammatory response of peritendinous tissue are also important causes of tendon adhesion. In addition, adhesions may cause a variety of complications, such as small intestinal obstruction, secondary infertility, pain at the site of onset, or joint movement dysfunction. Due to the serious complications that adhesions may cause, preventing the occurrence of adhesions is of great significance for improving the quality of life of patients and reducing medical costs.
[0003] At present, the anti-adhesion biofilm material used as a physical barrier can inhibit adhesion formation by isolating the injured part from the surrounding tissue, and it has become a commonly used method in clinical practice. At present, researchers have developed anti-adhesion membranes made of various biomaterials, including natural materials (such as collagen, hyaluronic acid), synthetic materials (such as polylactic acid, polyglycolic acid) and composite materials. These materials improve the tissue repair effect to a certain extent. For example, a decellularized pericardium reported in patent document CN116077739A has a double-sided structure that can effectively block adhesion. A composite nanofiber membrane proposed in CN111714696A has both good biocompatibility and mechanical properties.
[0004] However, existing anti-adhesion biofilm materials still have some shortcomings: most anti-adhesion biofilms need to be sutured and fixed, which increases the difficulty of surgical operation and the risk of infection. In addition, the degradation rate, mechanical strength and tissue biocompatibility of the material still need to be further optimized. Therefore, the development of an anti-adhesion biomaterial with self-adhesiveness, good biocompatibility and absorbability is of great significance for improving the effect of tissue repair. Summary of the invention
[0005] Therefore, the technical problem to be solved by the present invention is to overcome the defects of the prior art that the anti-adhesion biofilm material needs to be sutured and fixed, which increases the difficulty of surgical operation and the risk of infection, and the degradation rate, mechanical strength and tissue biocompatibility are difficult to be satisfactory, thereby providing a self-adhesive material and a preparation method and use thereof. The self-adhesive material can be suture-free due to its self-adhesiveness, and can reduce the difficulty of surgical operation and the risk of infection when applied to anti-adhesion membranes. The self-adhesive material is degradable and can be completely degraded and absorbed in the body of humans or non-human animals. It has good biocompatibility and adjustable mechanical properties. At the same time, the biomaterial can be endowed with multifunctional properties such as luminous positioning, drug delivery, repair promotion, antibacterial, and angiogenesis promotion.
[0006] To this end, the present invention provides the following technical solutions: The present invention provides a method for preparing a self-adhesive material, comprising: Component A and component B are reacted to form a citric acid-based prepolymer; component A is at least one compound having at least two reactive functional groups on the end group or side chain, the functional groups being the same or different; the functional groups are selected from at least one of hydroxyl, amino, thiol, epoxy, carboxyl, anhydride, and organic substituents; component B is citric acid and / or its derivatives; the reaction includes polycondensation, substitution, or transesterification; The citric acid-based prepolymer and isocyanate are subjected to a urethane bond or an amide bond cross-linking reaction.
[0007] Optionally, the isocyanate is selected from at least one of 1,6-hexamethylene diisocyanate, isophorone diisocyanate, toluene diisocyanate, lysine diisocyanate, naphthalene diisocyanate, 1,4-cyclohexyl diisocyanate, 4,4'-diphenylmethane diisocyanate or 4,4'-diisocyanate dicyclohexylmethane.
[0008] Optionally, the isocyanate is selected from at least one of 1,6-hexamethylene diisocyanate, lysine diisocyanate and isophorone diisocyanate.
[0009] Optionally, when the citric acid-based prepolymer is in a solid state, before the cross-linking reaction of the urethane bond or the amide bond is carried out, the citric acid-based prepolymer is dissolved in an organic solvent to obtain a citric acid-based prepolymer solution; isocyanate is added to the citric acid-based prepolymer solution to obtain a mixed solution, and then the cross-linking reaction of the urethane bond or the amide bond is carried out; The mass percentage of the citric acid-based prepolymer in the citric acid-based prepolymer solution is 30-60%; The mass percentage of the isocyanate added to the citric acid-based prepolymer is greater than 0% and less than or equal to 50%.
[0010] Optionally, the conditions for the cross-linking reaction of the urethane bond or amide bond are: the temperature is room temperature, the reaction time is 0 to 24 hours, and the reaction time is greater than 0 hours, ensuring that the added organic solvent is completely volatilized.
[0011] Optionally, the self-adhesive material is prepared into a film by spin coating, solution casting or tape casting a mixed solution of a citric acid-based prepolymer and isocyanate during a cross-linking reaction of urethane bonds or amide bonds.
[0012] Optionally, the spin coating conditions are a rotation speed of 1000-3000 rpm / min, a time of 0-3 min, and ≠0 min.
[0013] Optionally, the thickness of the film is 10-500 μm. A thinner film material can better fit the damaged tissue site, reduce the foreign body sensation, and is less subject to tension and can effectively maintain a self-adhesive state.
[0014] Optionally, the component A is a hydrophobic compound or a hydrophilic compound; And / or, when component A is a hydroxy compound, it includes but is not limited to ethylene glycol, hexylene glycol, octanediol, polyethylene glycol, bis(4-hydroxyphenyl) disulfide, resveratrol, bis(2-hydroxyethyl) disulfide, isosorbide, xylitol, glycolate or N-methyldiethanolamine; and / or, when component A is an amino acid or other compound containing an amino group or a thiol group, including but not limited to serine, phosphoserine, cysteine, glutamine or polyaniline; and / or, when component A is an epoxy compound, it includes but is not limited to epoxy soybean oil, epoxy resin, epichlorohydrin or lactide; and / or, when component A is a compound containing a carboxyl group or anhydride, it includes but is not limited to folic acid, tartaric acid, adipic acid, succinic acid, fumaric acid, salicylic acid, acetic anhydride or maleic anhydride; and / or, when the component A is a compound containing an organic substituent, it includes but is not limited to polyphosphazene; And / or, the citric acid and / or its derivatives include but are not limited to citric acid, trimethyl citrate, triethyl citrate, tributyl citrate, acetyl triethyl citrate, stearoyl monoglyceride citrate or citric acid luminescent molecules.
[0015] The invention provides a self-adhesive material prepared by the self-adhesive material preparation method.
[0016] The present invention provides the use of the self-adhesive material in any of the following: The invention is used for preparing a suture-free and / or anti-adhesion biological membrane; the suture-free and / or anti-adhesion biological membrane is a tissue anti-adhesion membrane used for tendons, abdominal cavity, pelvic cavity, nerves, and spinal cord.
[0017] The technical solution of the present invention has the following advantages: 1. A method for preparing a self-adhesive material provided by the present invention comprises: reacting component A and component B to form a citric acid-based prepolymer; component A is at least one compound having at least two reactive functional groups on the end group or side chain, the functional groups being the same or different; the functional groups being selected from at least one of hydroxyl, amino, thiol, epoxy, carboxyl, anhydride, and organic substituents; component B is citric acid and / or its derivatives; the reaction comprises a polycondensation reaction, a substitution reaction, or an ester exchange reaction; crosslinking the citric acid-based prepolymer with isocyanate to form an urethane bond or an amide bond; the present invention has found that by directly using isocyanate to form a citric acid-based prepolymer, the citric acid-based prepolymer can be crosslinked to form an urethane bond or an amide bond. Cross-linked citric acid-based prepolymer, the cross-linking point is an urethane bond or an amide bond, such as an isocyanate group reacting with a hydroxyl group to generate a urethane bond cross-link. Since the urethane bond or amide bond formed by cross-linking improves the hydrogen bond interaction between the contact surfaces of the materials, the contact surfaces of the obtained materials have good self-adhesion, and can be fixed without suturing during application, greatly reducing the difficulty of surgical operation and the risk of infection. The obtained material can be directly attached to the surface of the defect, effectively avoiding the disadvantages of traditional membranes requiring suturing and the possible inflammatory response caused by sutures abrading the tissue, greatly simplifying the surgical operation, reducing damage to the tissue, and improving the success rate of the operation; Furthermore, the self-adhesive material also has a satisfactory degradation rate, mechanical strength and tissue compatibility. The prepared citric acid-based material can be completely degraded in the body, and the exogenous citric acid released by degradation can promote the repair of the defect site through metabolic regulation; In summary, compared with the anti-adhesion membrane prepared from traditional synthetic materials, the citric acid-based material prepared by the present invention has low production cost, simple preparation method, better biocompatibility, stronger self-adhesion, simpler operation method and potential multifunctionality (such as antibacterial, in vivo imaging, repair promotion, etc.). This material has broad transformation and application prospects in the field of tissue defect repair, and can effectively prevent adhesion, promote tissue regeneration, and improve patients' postoperative function.
[0018] 2. A method for preparing a self-adhesive material provided by the present invention, comprising the isocyanate being selected from at least one of 1,6-hexamethylene diisocyanate, isophorone diisocyanate, toluene diisocyanate, lysine diisocyanate, naphthalene diisocyanate, 1,4-cyclohexyl diisocyanate, 4,4'-diphenylmethane diisocyanate or 4,4'-diisocyanate dicyclohexylmethane. By using isocyanate to directly crosslink a citric acid-based prepolymer, the urethane bond or amide bond formed by crosslinking improves the hydrogen bond interaction between the contact surfaces of the materials, so that the contact surfaces of the obtained materials have good self-adhesion, and can be fixed without suturing during application, greatly reducing the difficulty of surgical operation and the risk of infection. The above isocyanates can achieve this function by adjusting the addition ratio with the prepolymer. Furthermore, because the self-adhesive material needs to have the property of being windable, if it is too hard or too brittle, it will affect its winding performance. Therefore, if the selected isocyanate molecular structure is too rigid or the amount used is too much, it will cause the strength of the material to increase, which is not conducive to winding. It is easy to produce an obvious foreign body sensation when implanted in the body and easily induce an inflammatory reaction. The molecular structure of the above-mentioned isocyanate can ensure that the prepared self-adhesive material has the property of being windable. Furthermore, 1,6-hexamethylene diisocyanate, lysine diisocyanate and isophorone diisocyanate are isocyanates with a relatively flexible molecular chain structure, and the prepared self-adhesive materials have excellent windability.
[0019] 3. A method for preparing a self-adhesive material provided by the present invention comprises: when the citric acid-based prepolymer is in a solid state, before the cross-linking reaction of the urethane bond or amide bond is carried out, the citric acid-based prepolymer is dissolved in an organic solvent to obtain a citric acid-based prepolymer solution; isocyanate is added to the citric acid-based prepolymer solution to obtain a mixed solution, and then the cross-linking reaction of the urethane bond or amide bond is carried out; the mass percentage of the citric acid-based prepolymer in the citric acid-based prepolymer solution is 30-60%; the mass percentage of the isocyanate added to the citric acid-based prepolymer is greater than 0% and less than or equal to 50%. By controlling the ratio of the citric acid-based prepolymer and the isocyanate, the adhesion of the material can be improved, because: the urethane bond or amide bond formed by the isocyanate directly cross-linking the citric acid-based prepolymer improves the hydrogen bond interaction between the contact surfaces of the material, so that the contact surfaces of the obtained material have good self-adhesiveness, so the ratio of the citric acid-based prepolymer and the isocyanate will directly affect the content of hydrogen bonds, thereby affecting the adhesion performance of the material. Furthermore, because the self-adhesive material needs to have the property of being able to be wound, if it is too hard or too brittle, it will affect its winding performance. Therefore, if too much isocyanate is used, the strength of the material will increase, which is not conducive to winding. It is easy to produce an obvious foreign body sensation when implanted in the body and easily induce an inflammatory reaction. By selecting the above ratio, a self-adhesive material with better winding performance can be prepared.
[0020] 4. The present invention provides a method for preparing a self-adhesive material. When the self-adhesive material is prepared into a film, the method comprises spin coating a mixture of a citric acid-based prepolymer and an isocyanate during a cross-linking reaction of an ester bond or an amide bond to form a film; the spin coating is performed at a rotation speed of 1000 to 3000 rpm / min and a time of 0 to 3 min, and ≠0 min; by forming the film by spin coating, the solvent evaporates rapidly during the rapid rotation, thereby ensuring that the thickness of the prepared film is controllable and quickly dries.
[0021] 5. The present invention provides a method for preparing a self-adhesive material, wherein component A is a hydrophobic compound or a hydrophilic compound; the present invention prepares a hydrophilic or hydrophobic material by changing the structure of component A. In the present invention, when a compound such as octanediol is selected, a hydrophobic anti-adhesion biofilm can be obtained, and when a hydrophilic compound such as polyethylene glycol is selected, a hydrophilic anti-adhesion biofilm can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 This is a real-life rendering of the suture-free anti-adhesion membrane prepared according to Example 1.
[0024] Figure 2 The following are scanning electron microscope images of the surface and cross-section of the suture-free anti-adhesion membrane prepared according to Example 1.
[0025] Figure 3 The infrared spectrum of the suture-free anti-adhesion membrane prepared according to Example 1.
[0026] Figure 4 This is a self-adhesive effect diagram of the suture-free anti-adhesion film prepared according to Example 1.
[0027] Figure 5 The figures are as follows: the citric acid content released by the suture-free anti-adhesion membrane prepared by using the prepolymer prepared in Example 1 and different mass proportions of isocyanate, and the statistical graph of the citric acid content in the cells after co-incubation; the left side is the citric acid content released into the supernatant by the suture-free anti-adhesion membrane; the right side is the citric acid content in the cells after co-incubation of the supernatant and the cells.
[0028] Figure 6 Graph showing the water contact angle of the suture-free anti-adhesion membrane prepared in Example 2.
[0029] Figure 7 This is a self-adhesive effect diagram of the suture-free anti-adhesion film prepared according to Example 2.
[0030] Figure 8 The fluorescence absorption spectrum of the citrate prepolymer prepared according to Example 3 is shown in FIG.
[0031] Fig. 9 The mechanical properties of the suture-free anti-adhesion membranes prepared according to Examples 1 to 4.
[0032] Fig.10 The self-adhesive properties of the suture-free anti-adhesion membrane prepared according to the steps of Examples 1 to 4.
[0033] Fig.11 The cell compatibility of the suture-free anti-adhesion membrane prepared according to the steps of Examples 1 to 4.
[0034] Fig.12 The diagram shows the anti-protein adhesion effect of the suture-free anti-adhesion membrane prepared according to Examples 1 to 4.
[0035] Fig.13 The diagram shows the in vivo self-adhesive effect of the suture-free anti-adhesion membranes prepared according to Examples 2 and 4.
[0036] Fig.14 This is an in vivo tissue H&E staining section of the suture-free anti-adhesion membrane prepared according to Example 4.
[0037] Fig.15 The figure is a physical picture of the degradation of the suture-free anti-adhesion membrane prepared according to Example 4 in vivo.
[0038] Fig.16 is the synthesis equation for preparing a citric acid-based prepolymer according to step 1 of Examples 5 to 7.
[0039] Fig.17 This is a diagram showing the effect of the preparation according to the preparation method of Example 8.
[0040] Fig.18 This is a diagram showing the effect of the preparation according to the preparation method of Example 9.
[0041] Fig.19 is the tensile strength of the suture-free anti-adhesion membrane prepared according to Example 10.
[0042] Fig. 20 The self-adhesive strength of the suture-free anti-adhesion membrane prepared according to Example 12 and Comparative Example 1 was measured by immersing the prepared membrane material in PBS with a pH value of 7.4 to observe the wet adhesive performance.
[0043] Fig.21The self-adhesive properties of the suture-free anti-adhesion films prepared in Example 1 and Example 13 are compared. The thickness of the film material significantly affects the self-adhesive strength. DETAILED DESCRIPTION
[0044] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0045] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0046] The embodiment of the present invention discloses a method for preparing a self-adhesive material, comprising: reacting component A and component B to form a citric acid-based prepolymer; component A is at least one compound having at least two reactive functional groups on the end group or side chain, and the functional groups are the same or different; the functional groups are selected from at least one of hydroxyl, amino, thiol, epoxy, carboxyl, anhydride, and organic substituents; component B is citric acid and / or its derivatives; the reaction comprises a polycondensation reaction, a substitution reaction, or an ester exchange reaction; and the citric acid-based prepolymer and isocyanate are subjected to a crosslinking reaction of an urethane bond or an amide bond. The present invention has been found that isocyanate does not participate in the preparation process of polyester prepolymer. Isocyanate is directly cross-linked with citric acid-based prepolymer at the cross-linking point to form urethane bonds or amide bonds without thermal cross-linking. The obtained material has self-adhesion. The main reason is that the material mainly forms urethane bonds or amide bonds through isocyanate cross-linking, which can improve the hydrogen bond interaction between the contact surfaces of the materials to achieve self-adhesion. Therefore, when the material is applied to anti-adhesion membrane, sutures can be avoided to reduce the difficulty of surgical operation and the risk of infection. The material also has a satisfactory degradation rate, mechanical strength and tissue compatibility.
[0047] In some embodiments, the isocyanate is selected from at least one of 1,6-hexamethylene diisocyanate, isophorone diisocyanate, toluene diisocyanate, lysine diisocyanate, naphthalene diisocyanate, 1,4-cyclohexylene diisocyanate, 4,4'-diphenylmethane diisocyanate or 4,4'-diisocyanate dicyclohexylmethane. By using isocyanate to directly crosslink the citric acid-based prepolymer, the urethane bond or amide bond formed by crosslinking improves the hydrogen bond interaction between the material contact surfaces, so that the obtained material contact surfaces have good self-adhesion, and can be fixed without suturing during application, greatly reducing the difficulty of surgical operation and the risk of infection. The above isocyanates can achieve this function by adjusting the addition ratio with the prepolymer.
[0048] Furthermore, because the self-adhesive material needs to have the property of being able to be wound, if it is too hard or too brittle, it will affect its winding performance. Therefore, if the selected isocyanate molecular structure is too rigid or the amount used is too much, it will cause the strength of the material to increase, which is not conducive to winding. It is easy to produce an obvious foreign body sensation when implanted in the body and easily induce an inflammatory reaction. The above-mentioned isocyanate molecular structure can ensure that the prepared self-adhesive material has the property of being able to be wound.
[0049] In a preferred embodiment, the isocyanate is selected from at least one of 1,6-hexamethylene diisocyanate, lysine diisocyanate and isophorone diisocyanate. The molecular structures of 1,6-hexamethylene diisocyanate, lysine diisocyanate and isophorone diisocyanate are less rigid than diisocyanates with branched or cyclic structures, so the upper limit of the amount added is higher when adjusting the ratio, and more hydrogen bond structures can be introduced, so that the self-adhesive properties of the material are also increased accordingly.
[0050] In some embodiments, when the citric acid-based prepolymer is in a solid state, before performing a cross-linking reaction of an urethane bond or an amide bond, the citric acid-based prepolymer is dissolved in an organic solvent to obtain a citric acid-based prepolymer solution; isocyanate is added to the citric acid-based prepolymer solution to obtain a mixed solution, and then a cross-linking reaction of an urethane bond or an amide bond is performed; the mass percentage of the citric acid-based prepolymer in the citric acid-based prepolymer solution is 30-60%; the mass percentage of the isocyanate added to the citric acid-based prepolymer is >0% and ≤50%. Further, the mass percentage of the citric acid-based prepolymer in the citric acid-based prepolymer solution can be any one of 30%, 33%, 35%, 38%, 40%, 43%, 45%, 48%, 50%, 53%, 55%, 58%, and 60%, or a range between any two values; the mass percentage of the isocyanate addition to the citric acid-based prepolymer can be any one of 0.01%, 0.1%, 0.5%, 1%, 5%, 8%, 10%, 13%, 15%, 18%, 20%, 23%, 25%, 28%, 30%, 33%, 35%, 38%, 40%, 45%, 48%, and 50%, or a range between any two values. By controlling the ratio of citric acid-based prepolymer and isocyanate, the adhesion of the material can be improved. The reason is that the urethane bond or amide bond formed by isocyanate directly cross-linking the citric acid-based prepolymer improves the hydrogen bond interaction between the contact surfaces of the materials, so that the contact surfaces of the obtained materials have good self-adhesion. Therefore, the ratio of citric acid-based prepolymer and isocyanate will directly affect the content of hydrogen bonds, thereby affecting the adhesion performance of the material. Further, because the self-adhesive material needs to have the ability to be wound, if it is too hard or too brittle, it will affect its winding performance. Therefore, if the amount of isocyanate selected is too much, it will cause the strength of the material to increase, which is not conducive to winding. It is easy to produce a significant foreign body sensation when implanted in the body and easily induce an inflammatory reaction. Selecting the above ratio can prepare a self-adhesive material with better winding performance.
[0051] In some embodiments, the prepolymer prepared with citric acid as component B is solid and requires an anhydrous organic solvent for dissolution. Examples of suitable organic solvents include acetone, dioxane, cyclohexane or isopropyl ether, etc. The mass ratio of the prepolymer to the organic solvent is 30-60%, and the preferred organic solvent is dioxane. In one embodiment, the prepolymer prepared with a citrate ester as component B is liquid and does not require an organic solvent for dissolution.
[0052] In some embodiments, the conditions for the cross-linking reaction of the urethane bond or the amide bond are: room temperature, 0~24h, and the reaction time is greater than 0h, ensuring that the added organic solvent is completely volatilized. Further, the reaction time can be greater than 0 min, 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5h, 5 h, 5.5 h, 6 h, 6.5 h, 7 h, 7.5 h, 8 h, 8.5 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h, 15 h, 16 h, 17 h, 18 h, 19 h, 20 h, 21 h, 22 h, 23 h, 24 h, any one of the values or the range value between any two values. The method of the present invention is carried out at room temperature, without heating, and the reaction is rapid. The temperature range of room temperature is 10-30°C, including but not limited to 10°C, 15°C, 20°C, 25°C, and 30°C.
[0053] In some embodiments, the self-adhesive material is prepared into a film by spin coating, solution casting or tape casting a mixture of a citric acid-based prepolymer and an isocyanate during a cross-linking reaction of urethane bonds or amide bonds.
[0054] In some embodiments, the spin coating condition is a rotation speed of 1000-3000 rpm / min, a time of 0-3 min, and ≠0 min. Further, the rotation speed can be any one of 1000 rpm / min, 1100 rpm / min, 1200 rpm / min, 1500 rpm / min, 1800 rpm / min, 2000 rpm / min, 2200 rpm / min, 2500 rpm / min, 2800 rpm / min, 3000 rpm / min, or a range between any two values; the time can be any one of 0.01 min, 0.1 min, 0.5 min, 0.8 min, 1 min, 1.2 min, 1.5 min, 1.8 min, 2.0 min, 2.2 min, 2.5 min, 2.8 min, 3 min, or a range between any two values.
[0055] Furthermore, in some embodiments, after spin coating, solution casting or tape casting, the film is further cross-linked under ultraviolet light, so that a film material that can be photocross-linked or 3D printed can be prepared. The ultraviolet light condition can be 365 nm ultraviolet light for 1 to 3 min.
[0056] In some embodiments, the component A is a hydroxy compound, including but not limited to polyols and ethers. The polyol is such as a diol. The diol includes but is not limited to aliphatic alkane diols of C2-C20, C2-C12 or C2-C6, including α,ω-n-alkane diol or α,ω-olefin diol. Further, the hydroxy compound includes but is not limited to ethylene glycol, hexanediol, octanediol, polyethylene glycol, bis(4-hydroxyphenyl) disulfide, resveratrol, bis(2-hydroxyethyl) disulfide, isosorbide, xylitol, glycolic acid ester or N-methyldiethanolamine.
[0057] In some embodiments, when the component A is an amino acid or other compound containing an amino group or a thiol group, it includes but is not limited to serine, phosphoserine, cysteine, glutamine, polyaniline, and the like.
[0058] In some embodiments, when the component A is an epoxy compound, it includes but is not limited to epoxy soybean oil, epoxy resin, epichlorohydrin, lactide, and the like.
[0059] In some embodiments, when the component A is a compound containing a carboxyl group or anhydride, it includes but is not limited to folic acid, tartaric acid, adipic acid, succinic acid, fumaric acid, salicylic acid, acetic anhydride, maleic anhydride, and the like.
[0060] In some embodiments, when the component A is a compound containing an organic substituent, it includes but is not limited to polyphosphazene and the like.
[0061] In some embodiments, the citric acid and / or its derivatives include but are not limited to citric acid, trimethyl citrate, triethyl citrate, tributyl citrate, acetyl triethyl citrate, stearoyl monoglyceride citrate, and citric acid luminescent molecules (such as CA-Cys).
[0062] In some embodiments, the component A is a hydrophobic compound or a hydrophilic compound. When the component A is a hydrophilic compound (such as polyethylene glycol), the prepared material is a hydrophilic material. When the component A is a hydrophobic compound (such as octanediol), the prepared material is a hydrophobic material.
[0063] In some embodiments, when component A containing amino acids reacts with citric acid to generate fluorescent light-emitting groups, materials with fluorescent functions can be prepared for applications such as biological imaging and positioning.
[0064] In some embodiments, by adjusting the ratio of the citric acid-based prepolymer or the isocyanate, or the molecular structure of the isocyanate, the mechanical strength of the material can be regulated, and the strength of the anti-adhesion membrane for tissue can be significantly improved.
[0065] In some embodiments, the functional groups of the side chains of the citric acid-based prepolymer can also load antibacterial drugs, promote nerve regeneration or promote tissue repair, or various types of drugs can be encapsulated during the cross-linking process to adapt to the repair of different defect sites, thereby preparing materials with drug delivery functions, such as tissue anti-adhesion films.
[0066] In some embodiments, component A of dicarboxylic acid, unsaturated fatty acid or anhydride can react with citric acid to prepare a photo-crosslinkable citric acid-based prepolymer, which can be prepared by 3D printing to adapt to the size and shape of different defect sites, and can be used to prepare a tissue anti-adhesion film with photo-crosslinking or 3D printing function.
[0067] In some embodiments, citric acid is used as component B, and the molar ratio of citric acid to the compound containing hydroxyl, amino, thiol, epoxy, carboxyl, anhydride, organic substituent, etc. in the side chain or terminal group of component A is 1-2, the polymerization temperature is 140-160°C, the polymerization time is 0-6 h, and greater than 0 h, and the rotation speed is 100-1000 rpm / min. Further, the polymerization temperature can be any one of 140, 142, 145, 148, 150, 153, 155, 158, 160°C or a range between any two values. The rotation speed can be any one of 100, 200, 500, 600, 800, 1000 rpm / min or a range between any two values. The reaction time can be any one of 0.1 min, 1 min, 5 min, 10 min, 20 min, 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, or a range between any two of the values.
[0068] In some embodiments, the molar ratio of citrate as component B to the compound containing hydroxyl groups in the side chain or terminal group of component A is 1 to 2, the polymerization temperature is 140 to 160°C, the polymerization time is 0 to 48 h, and greater than 0 h, and the rotation speed is 100 to 1000 rpm / min. Further, the polymerization temperature can be any one of 140, 142, 145, 148, 150, 153, 155, 158, 160°C or a range between any two values. The rotation speed can be any one of 100, 200, 500, 600, 800, 1000 rpm / min or a range between any two values. The reaction time can be any one of 0.1 min, 1 min, 5 min, 10 min, 20 min, 0.5 h, 1 h, 2, 4, 6, 8, 10, 12, 14, 16, 18, 20, 22, 24, 26, 28, 30, 32, 34, 36, 38, and 48 h, or a range between any two of the values.
[0069] The embodiment of the present invention provides the use of the self-adhesive material in any of the following: (1) Use in preparing suture-free and / or anti-adhesion biofilms; (2) The suture-free and / or anti-adhesion biological membrane can be used as an anti-adhesion membrane for tissues in tendons, abdominal cavity, pelvic cavity, nerves, and spine.
[0070] The alcohols used in the following examples, such as hexanediol, octanediol, cyclohexane, etc., and cysteine were of analytical grade.
[0071] Example 1 An example of preparing a citric acid-based polymer by polycondensation of citric acid and polyols, and crosslinking with diisocyanate to form a film.
[0072] (1) 10 g of citric acid and 7 g of 1,6-hexanediol were added to a flask, the speed was set to 800 rpm / min, and the reaction was carried out at 140°C for 3 h. The reactants were precipitated with deionized water and freeze-dried to obtain a citrate prepolymer; (2) Accurately quantify the mass of the prepolymer and add cyclohexane to obtain a prepolymer solution with a mass fraction of 50%; (3) Take a solution containing 1 g of prepolymer and add 20% of 1,6-hexamethylene diisocyanate (i.e., add 100 mg of 1,6-hexamethylene diisocyanate to 0.5 g of prepolymer), and spin coat it on a spin coater at a speed of 1000 rpm / min for 1 min to form a film. After the film is dry, remove it to obtain a suture-free anti-adhesion film.
[0073] The obtained suture-free anti-adhesion membrane was tested for various indicators, and the test results are as follows: Figure 1 This is a real-life rendering of the suture-free anti-adhesion membrane prepared according to step (3) of Example 1.
[0074] Figure 2 This is a scanning electron microscope image of the surface and thickness of the suture-free anti-adhesion membrane prepared according to step (3) of Example 1. It can be seen from the image that the membrane prepared by this preparation method has a dense and smooth surface and no pore structure, which can effectively prevent the growth of fibroblasts.
[0075] Figure 3 The infrared spectra of the suture-free anti-adhesion membrane (cross-linked group) prepared according to step (3) of Example 1 and the citrate prepolymer (uncross-linked group) prepared according to step (1) are shown in FIG. The infrared spectra of the cross-linked group are shown in FIG. -1 A new characteristic peak appeared at , which was attributed to the characteristic absorption peak of -NH- in carbamate, indicating that the membrane was prepared by chemical cross-linking. Figure 4This is a self-adhesive effect diagram of the suture-free anti-adhesion membrane prepared according to Example 1. The picture shows that the membrane can be overlapped together through hydrogen bonding with each other to form a self-entanglement, thereby eliminating the experimental step of suturing.
[0076] Figure 5 The citric acid content released by the suture-free anti-adhesion membrane prepared by using the prepolymer prepared in Example 1 and different mass ratios of isocyanate, and the statistical graph of the citric acid content in the cells after co-incubation; Figure 5 The left side shows the citric acid content released into the supernatant by the suture-free anti-adhesion membrane; Figure 5 The right side of is the citric acid content in the cells after the supernatant and cells are co-incubated. The specific method is: according to step (3) of Example 1, different mass percentages of 1,6-hexamethylene diisocyanate (0%, 5%, 10%, 15%, 20%) are added to the prepolymer solution prepared in step (2) to form a self-adhesive anti-adhesion membrane after cross-linking, and the membrane with a diameter of 8 mm is immersed in 1 mL of PBS (pH=7.4), placed in a 37°C incubator for 24 hours, and the citric acid content in the supernatant of the extract is then detected. Under the same conditions, the culture medium is used for extraction, and the supernatant is taken and co-cultured with mouse embryonic fibroblasts (NIH / 3T3), that is, 10,000 cells are added to each well of 96T for co-culture for 24 hours, and after 24 hours, 100 μL of the above-mentioned extract is replaced in each well and co-culture is continued for 24 hours, and then washed with PBS with pH=7.4, and the citric acid content in the cells is measured after lysis and centrifugation. The results showed that membranes with a high degree of cross-linking degraded slowly and released less citric acid, which led to a corresponding decrease in the intracellular citric acid content.
[0077] Example 2 The difference between this embodiment and embodiment 1 is that the mass of 1,6-hexamethylene diisocyanate is replaced by lysine diisocyanate to prepare a strength-adjustable membrane.
[0078] The obtained suture-free anti-adhesion membrane was tested for various indicators, and the test results are as follows: The obtained suture-free anti-adhesion membrane was subjected to water contact angle test according to the national standard GB / T 30693-2014. Figure 6 This is a water contact angle picture of the suture-free anti-adhesion membrane prepared according to Example 2. The result shows that the water contact angle of the membrane is 109.5°, which indicates that the introduction of the long alkyl chain of hexanediol makes the membrane hydrophobic and has an anti-fouling effect.
[0079] Figure 7The self-adhesive effect diagram and adhesive stability test of the suture-free anti-adhesion film prepared in Example 2. The test method is: wrap the suture-free anti-adhesion film on the outside of a 1 mL syringe to simulate the wrapping effect on the tendon part. The length of the material film is slightly longer than the circumference of the syringe. Through the overlap of the film and the film itself, the film material can stably wrap the outer surface of the syringe without falling off (see Figure 7 The whole thing was then immersed in PBS at pH 7.4 and placed in a shaker at 37°C for 1 month. The results showed that ( Figure 7 (On the right side of the figure) Even in a wet environment, the film still has a good wrapping effect on the surface of the syringe and does not fall off, which indicates that the film has good long-term stability in a wet environment and has the potential for application in a wet environment in vivo.
[0080] Example 3 An example of preparing a citric acid-based polymer by polycondensation of citric acid with amino acids and crosslinking with diisocyanate to prepare an imageable film.
[0081] (1) Add 10 g of citric acid and 6 g of cysteine into a flask, set the speed to 800 rpm / min, react at 140°C for 4 h, precipitate the reactants with deionized water, and obtain a citrate prepolymer by freeze-drying; (2) Accurately quantify the mass of the prepolymer and add cyclohexane to obtain a prepolymer solution with a mass fraction of 50%; (3) Take 1 g of the prepolymer solution, add 20% by weight of 1,6-hexamethylene diisocyanate to the prepolymer, and spin coat the solution on a spin coater at a speed of 1000 rpm / min for 1 min to form a film. After the film is dry, remove it to obtain a suture-free anti-adhesion film.
[0082] The citrate prepolymer obtained in step (1) was subjected to fluorescence absorption spectrum detection, with an excitation wavelength of 350 nm and an emission wavelength of 420 nm. The detection results are as follows: Figure 8 As shown, Figure 8 This is the fluorescence absorption spectrum of the citrate prepolymer prepared according to the steps of Example 3, which proves that the reaction of molecules containing amino groups such as amino acids and citric acid can generate fluorescent light-emitting groups. By using different amino acids or molecules containing amino groups, a series of photoluminescent fluorescent molecules can be obtained, which can be used to prepare a series of citric acid-based degradable polymer photoluminescent suture-free anti-adhesion films with adjustable excitation and emission wavelengths (visible light-near infrared) for applications such as biological imaging.
[0083] Example 4 An example of preparing citric acid-based polymers by transesterification of citric acid esters with polyols and crosslinking with diisocyanates to form films.
[0084] (1) 10 g of triethyl citrate and 6 g of 1,6-hexanediol were added to a flask, the speed was set to 800 rpm / min, and the reaction was carried out at 140°C for 24 h. The reactants were precipitated with deionized water and freeze-dried to obtain a liquid citrate prepolymer; (2) Take 1 g of the prepolymer solution, add 20% by weight of 1,6-hexamethylene diisocyanate to the prepolymer, and spin coat the solution on a spin coater at a speed of 1000 rpm / min for 1 min to form a film. After the film is dry, remove it to obtain a suture-free anti-adhesion film.
[0085] Example 5 An example of preparing a citric acid-based polymer by polycondensation reaction of citric acid with polyols and anhydrides, and forming a film by crosslinking with diisocyanate and UV.
[0086] (1) 8 g of citric acid, 2 g of maleic anhydride and 7 g of octanediol were added to a flask, the speed was set to 800 rpm / min, and the reaction was carried out at 140°C for 3 h. The reactants were precipitated with deionized water and freeze-dried to obtain a citrate prepolymer; (2) Accurately quantify the mass of the prepolymer and add cyclohexane to obtain a prepolymer solution with a mass fraction of 50%; (3) Take 1 g of the prepolymer solution, add 5% by mass of 1,6-hexamethylene diisocyanate to the prepolymer, and spin coat the solution on a spin coater at a speed of 1000 rpm / min for 1 min to form a film. Irradiate the film with 365 nm ultraviolet light for 3 min to further crosslink it. After the film is dry, remove it to obtain a suture-free anti-adhesion film.
[0087] Example 6 An example of preparing a citric acid-based polymer by polycondensation of citric acid and polyamine, and crosslinking with diisocyanate to form a film.
[0088] (1) Add 10 g of citric acid and 6 g of hexamethylenediamine into a flask, set the speed to 800 rpm / min, react at 140°C for 3 h, precipitate the reactants with deionized water, and obtain a citrate prepolymer by freeze-drying; (2) Accurately quantify the mass of the prepolymer and add cyclohexane to obtain a prepolymer solution with a mass fraction of 50%; (3) Take 1 g of the prepolymer solution, add 10% by weight of 1,6-hexamethylene diisocyanate to the prepolymer, and spin coat the solution on a spin coater at a speed of 1000 rpm / min for 1 min to form a film. After the film is dry, remove it to obtain a suture-free anti-adhesion film.
[0089] Example 7 An example of preparing citric acid-based polymers by condensation polymerization of citric acid and polycarboxylic acids, and cross-linking with diisocyanate to form films.
[0090] (1) Add 10 g of citric acid and 7 g of adipic acid into a flask, set the speed to 800 rpm / min, react at 140°C for 3 h, precipitate the reactants with deionized water, and obtain a citrate prepolymer by freeze-drying; (2) Accurately quantify the mass of the prepolymer and add cyclohexane to obtain a prepolymer solution with a mass fraction of 50%; (3) Take 1 g of the prepolymer solution, add 10% by weight of 1,6-hexamethylene diisocyanate to the prepolymer, and spin coat the solution on a spin coater at a speed of 1000 rpm / min for 1 min to form a film. After the film is dry, remove it to obtain a suture-free anti-adhesion film.
[0091] Fig.16 is the synthesis equation for preparing the citric acid-based prepolymer according to step (1) of Examples 5 to 7.
[0092] Example 8 A suture-free anti-adhesion membrane was prepared in the same manner as in Example 2, except that the membrane was spin-coated at a speed of 500 rpm / min.
[0093] Results: The film state after spin coating was observed. Since the prepolymer solution is hydrophobic and has a high viscosity, it is difficult to apply the coating evenly at a low rotation speed. Fig.17 .
[0094] Example 9 A suture-free anti-adhesion membrane was prepared in the manner of Example 4, except that the ratio of the added 1,6-hexamethylene diisocyanate to the prepolymer was 100%.
[0095] Results: Due to the high ratio of isocyanate, the reaction rate between the prepolymer and isocyanate was too fast, and the spin coating liquid solidified quickly, making it difficult to spin coat. Fig.18 .
[0096] Example 10 The difference between this embodiment and embodiment 1 is that toluene diisocyanate of equal mass is used to replace 1,6-hexamethylene diisocyanate.
[0097] Results: Due to the high rigidity of the molecular structure of toluene diisocyanate, the strength of the prepared membrane was as high as 33.68 MPa. It could not be bent for self-winding and was not compatible with the surrounding tissues when implanted in the body. It was easy to induce inflammatory reactions and was not suitable for in vivo application. Fig.19 .
[0098] Embodiment 11 A suture-free anti-adhesion membrane was prepared in the manner of Example 1, except that polyethylene glycol 1000 of equal mass was used to replace 1,6-hexanediol, but no membrane could be formed at this cross-linking ratio.
[0099] Example 12 A suture-free anti-adhesion membrane was prepared in the manner of Example 1, except that: (3) 5% by weight of 1,6-hexamethylene diisocyanate was added to 1 g of the prepolymer solution.
[0100] Results: Due to the low cross-linking ratio, the hydrogen bonding sites for self-adhesion are insufficient, so the self-adhesion performance of the material is poor. It produces self-adhesion effect in the dry state, but once immersed in PBS with pH = 7.4, the self-adhesion site shifts and falls off, and the self-adhesion effect is lost. Fig. 20 .
[0101] Embodiment 13 A suture-free anti-adhesion membrane was prepared in the manner of Example 1, except that the system of the membrane-forming liquid was expanded by 5 times, i.e., 20% by mass of 1,6-hexamethylene diisocyanate was added to 5 g of the prepolymer solution (i.e., 500 mg of hexamethylene diisocyanate was added to 2.5 g of the prepolymer), and then the membrane was spin-coated.
[0102] Results: The coating thickness was measured with a vernier caliper and was about 720 μm. The excessive thickness of the film material resulted in excessive surface tension of the film, and the hydrogen bonding at the film bonding point could not maintain a good self-adhesive effect, and the film material lost its self-adhesive properties. At the same time, since the film material is relatively thick, it has an obvious foreign body sensation when in contact with skin tissue and is not suitable for use inside tissues. The coating thickness of the film material in Example 1 is about 100 μm, which can be effectively self-adhesive on the finger area and does not collapse when bent, and has good self-adhesive properties. Therefore, the thickness of the film material is also closely related to the self-adhesive properties, see Fig.21 .
[0103] Comparative Example 1 A suture-free anti-adhesion membrane was prepared in the manner of Example 1, except that isocyanate crosslinking was not used, and thermal crosslinking was used alone, that is, 1 g of the prepolymer solution was spin-coated on a spin coater at a speed of 1000 rpm / min for 1 min to form a film, which was then placed in an oven at 80°C for thermal crosslinking, and the film was removed after it was dried to obtain a suture-free anti-adhesion membrane.
[0104] Results: With thermal cross-linking, the membrane material is only cross-linked by ester bonds, lacks hydrogen bonding sites, and has poor self-adhesive properties. Fig. 20 .
[0105] Experimental Example 1 This experimental example investigates the various properties of the suture-free anti-adhesion membranes prepared in Examples 1 to 4 The test method is: the membrane material is made into a 1.5 cm wide and 4 cm long strip, placed on a universal testing machine, clamped 0.5 cm above and below, and stretched at a rate of 50 mm / min. Fig. 9As shown, Fig. 9 The mechanical properties of the suture-free anti-adhesion membrane prepared according to Examples 1 to 4 have a tensile strength of 50 to 100 KPa, which can be regulated by adjusting the molecular structure of isocyanate, matching the mechanical properties of commercially available materials, and meeting the support function at the tendon injury site.
[0106] The test method is: use two pieces of suture-free anti-adhesion membranes of the same preparation, overlap the two membranes face to face, and apply uniform pressure on the entire overlapping surface. The recommended applied pressure can reach 1 MPa, forming a T-shape. Fig.10 On the left side, the strength of the bonding joint is measured, referring to the national standard GB / T 2791-1995.
[0107] like Fig.10 The right side is the self-adhesive property of the suture-free anti-adhesion film prepared according to the steps of Examples 1 to 4. The results show that the prepared film has self-adhesiveness with a strength of 0.14 to 0.22 MPa, and its bonding strength can be adjusted by regulating the molecular structure of isocyanate.
[0108] The detection method is as follows: the suture-free anti-adhesion membrane (8 mm diameter) prepared in each embodiment is soaked in 1 mL of DMEM culture medium, placed in an incubator at 37°C for 24 h to obtain an extract, and then the extract is used to replace an equal volume of cell supernatant and co-cultured with mouse embryonic fibroblasts (NIH / 3T3), that is, 10,000 cells are added to each well of 96T for co-culture for 24 h, and after 24 h, 100 μL of extract is replaced in each well and co-culture is continued for 24 h. CCK8 is used to detect the OD 600 The absorbance value was read at nm for determination, where the live group was replaced with cell culture medium, and the dead group was replaced with sterile water. The cell survival rate was calculated as follows: Cell viability = (OD 材料组 -OD 全死组 ) / (OD 全活组 -OD 全死组 )×100%.
[0109] like Fig.11 The cytotoxicity of the suture-free anti-adhesion membrane prepared according to the steps of Examples 1 to 4 was tested. The results showed that the cell survival rates of all groups were higher than 70%, which indicates that the citric acid-based suture-free anti-adhesion membrane prepared by this preparation method has good biocompatibility and can be used for further characterization in vivo.
[0110] (4) Anti-protein adhesion effect The detection method is as follows: the membrane with a diameter of 8 mm prepared in each example is placed in the well of a 48-well plate, FITC-labeled BSA is prepared into a 2 mg / mL solution with PBS, 200 microliters is added to each well, and a control group is set up at the same time, the control group uses a commercially available membrane material (Seprafilm®), incubated at 37°C for 2 h, washed with PBS and observed with a fluorescence microscope.
[0111] like Fig.12 The diagram is a diagram showing the anti-protein adhesion effect of the suture-free anti-adhesion membrane prepared according to the steps of Examples 1 to 4. The results show that the citric acid-based suture-free anti-adhesion membrane prepared by the preparation method can effectively prevent the adhesion of proteins on its surface and play a good anti-adhesion role.
[0112] Experimental Example 2 This experimental example investigates the anti-adhesion effect of the suture-free anti-adhesion membrane in a tendon injury model Application in tendon injury model: SD rats weighing about 200-250 g were used for in vivo tendon injury animal modeling. The rats were anesthetized with sodium pentobarbital, the hair on the surface of the Achilles tendon was removed, and then disinfected with iodine tincture. The skin was cut longitudinally along the Achilles tendon, and the Achilles tendon was cut transversely. It was wrapped with a film of 1.0 cm × 2.0 cm in width × length, and then the skin was sutured and disinfected again. The film was a suture-free anti-adhesion film prepared in the steps of Examples 2 and 4, and the control group was sutured with surgical thread.
[0113] like Fig.13 The figure is a wrapping effect diagram of the suture-free anti-adhesion membrane prepared according to Examples 2 and 4 on the injured tendon of rats. The results show that the membrane prepared by the method of Examples 2 and 4 can effectively wrap the injured tendon without suturing, which greatly shortens the operation time and avoids the risk of infection. The control group needs surgical suturing to ensure docking repair.
[0114] Fig.14 The tissue H&E staining section after the suture-free anti-adhesion membrane prepared in Example 4 was wrapped around the injured part of the rat tendon for 1 day showed that a large number of inflammatory cells infiltrated the control group, while the membrane prepared by the method of Example 4 had good biocompatibility in vivo. In addition, there was an obvious gap between the tendon and the muscle, indicating that the citric acid-based suture-free anti-adhesion membrane had a good anti-adhesion effect in vivo and could effectively avoid the occurrence of fiber adhesion.
[0115] Fig.15 This is a macroscopic observation picture of the suture-free anti-adhesion membrane prepared according to Example 4 after being wrapped around the injured part of rat tendon for 9 weeks. The results show that the membrane is completely degraded at 9 W. This result indicates that the citric acid-based anti-adhesion membrane prepared by this method is completely degradable in vivo, has good biocompatibility, and will not accumulate in the internal tissues or organs of the human body.
[0116] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A method for preparing a self-adhesive material, characterized in that: include: reacting component A and component B to form a citric acid based prepolymer; Component A is at least one compound having at least two reactive functional groups on the terminal group or side chain, the functional groups being the same or different; the functional groups being at least one selected from hydroxyl, amino, thiol, epoxy, carboxyl, anhydride, and organic substituents; component B is citric acid and / or its derivatives; the reaction comprises polycondensation, substitution, or transesterification; The citric acid-based prepolymer and isocyanate are subjected to a urethane bond or an amide bond cross-linking reaction.
2. The method for preparing a self-adhesive material according to claim 1, characterized in that: The isocyanate is selected from at least one of 1,6-hexamethylene diisocyanate, isophorone diisocyanate, toluene diisocyanate, lysine diisocyanate, naphthalene diisocyanate, 1,4-cyclohexyl diisocyanate, 4,4'-diphenylmethane diisocyanate and 4,4'-diisocyanate dicyclohexylmethane.
3. The method for preparing a self-adhesive material according to claim 2, characterized in that: The isocyanate is selected from at least one of 1,6-hexamethylene diisocyanate, lysine diisocyanate and isophorone diisocyanate.
4. The method for preparing a self-adhesive material according to any one of claims 1 to 3, characterized in that: When the citric acid-based prepolymer is in a solid state, before the cross-linking reaction of the urethane bond or the amide bond is carried out, the citric acid-based prepolymer is dissolved in an organic solvent to obtain a citric acid-based prepolymer solution; isocyanate is added to the citric acid-based prepolymer solution to obtain a mixed solution, and then the cross-linking reaction of the urethane bond or the amide bond is carried out; The mass percentage of the citric acid-based prepolymer in the citric acid-based prepolymer solution is 30-60%; The mass percentage of the isocyanate added to the citric acid-based prepolymer is greater than 0% and less than or equal to 50%.
5. The method for preparing a self-adhesive material according to any one of claims 1 to 3, characterized in that: The conditions for the cross-linking reaction of the urethane bond or amide bond are: the temperature is room temperature, the reaction time is 0 to 24 h, and the reaction time is greater than 0 h.
6. The method for preparing a self-adhesive material according to any one of claims 1 to 3, characterized in that: When the self-adhesive material is prepared into a film, the mixed solution of citric acid-based prepolymer and isocyanate is subjected to spin coating, solution casting or tape casting to form a film during the cross-linking reaction of urethane bonds or amide bonds.
7. The method for preparing a self-adhesive material according to claim 6, characterized in that: The spin coating conditions are as follows: a rotation speed of 1000-3000 rpm / min, a time of 0-3 min, and ≠0 min; And or, the film has a thickness of 10-500 μm.
8. The method for preparing a self-adhesive material according to any one of claims 1 to 3, characterized in that: The component A is a hydrophobic compound or a hydrophilic compound; And / or, when component A is a hydroxy compound, it includes but is not limited to ethylene glycol, hexylene glycol, octanediol, polyethylene glycol, bis(4-hydroxyphenyl) disulfide, resveratrol, bis(2-hydroxyethyl) disulfide, isosorbide, xylitol, glycolate or N-methyldiethanolamine; and / or, when component A is an amino acid or other compound containing an amino group or a thiol group, including but not limited to serine, phosphoserine, cysteine, glutamine or polyaniline; and / or, when component A is an epoxy compound, it includes but is not limited to epoxy soybean oil, epoxy resin, epichlorohydrin or lactide; and / or, when component A is a compound containing a carboxyl group or anhydride, it includes but is not limited to folic acid, tartaric acid, adipic acid, succinic acid, fumaric acid, salicylic acid, acetic anhydride or maleic anhydride; And / or, when the component A is a compound containing an organic substituent, it includes but is not limited to polyphosphazene; And / or, the citric acid and / or its derivatives include but are not limited to citric acid, trimethyl citrate, triethyl citrate, tributyl citrate, acetyl triethyl citrate, stearoyl monoglyceride citrate or citric acid luminescent molecules.
9. A self-adhesive material prepared by the method for preparing a self-adhesive material according to any one of claims 1 to 8.
10. The self-adhesive material according to claim 9 is used for the following purposes: The invention relates to a use of a suture-free and / or anti-adhesion biofilm in the preparation of a suture-free and / or anti-adhesion biofilm; the suture-free and / or anti-adhesion biofilm is used as a tissue anti-adhesion membrane for tendons, abdominal cavity, pelvic cavity, nerves, and spinal cord.
Citation Information
Patent Citations
Composite tendon adhesion preventing membrane and preparation method
CN111714696A
Decellularized pericardium as well as preparation method and application thereof
CN116077739A
Water-borne dispersions of oil modified urethane polymers
CN101048477A
Preparation method of citric acid modified waterborne polyurethane dispersion
CN115594839A
Isocyanate-terminated prepolymer, preparation method and application thereof, and polyurethane adhesive containing isocyanate-terminated prepolymer
CN116023623A
Cited By
Self-adhesive material, and preparation method therefor and use thereof
WO2026174637A1